Short- and Long-Term Growth Response to Multiple Drought Episodes: Evidence of Genetic Adaptation in a Conifer Species - Sebastian-Alcona, Jaime; Cappa, Eduardo Pablo; Da Ros, Letitia; Ratcliffe, Blaise; Chen, Charles; Wei, Xiaojing; Liu, Yang; Mansfield, Shawn; Hamann, Andrea; El-Kassaby, Yousry A.; Thomas, Barh (Wiley, 2025)
Drought tolerance of tree species is a concern in the context of climate change, and tree ring analyses can be used to assess past growth response(s), to drought events. In the current study, we applied this approach to 1281 individuals with known pedigree in long-term genetic test plantations of lodgepole pine in western Canada. We assessed resistance, resilience, and recovery metrics, and analyzed their causal relationships with long-term growth and susceptibility to disease through structural equation modeling. We found that trees with low short-term resilience to drought events also experienced severe reductions in long-term growth. Narrow-sense heritability of drought tolerance metrics was low for short-term responses at specific sites, while a new long-term decline index for families showed moderate heritability ( of 0.15 to 0.30 ± 0.03). We also detected evidence of local adaptation, with trees from lower elevation showing better drought adaptation. We conclude that the selection of genotypes for drought tolerance is possible, and that other species or populations could be screened using this method. We also note that the new long-term decline index developed in this study shows a higher degree of genetic control than other metrices, and may therefore be of broader interest in dendrochronological research.